2004
DOI: 10.1128/jvi.78.22.12489-12496.2004
|View full text |Cite
|
Sign up to set email alerts
|

The VP6 Protein of Rotavirus Interacts with a Large Fraction of Human Naive B Cells via Surface Immunoglobulins

Abstract: Immunity to human group A rotavirus (RV), a major cause of viral gastroenteritis in infants, involves B lymphocytes that provide RV-specific antibodies. Additionally, some arguments suggest that naive B cells could be implicated in the first steps of the immune response against RV. The aim of our study was to analyze the interaction of VP6 and VP7 RV capsid proteins with human B cells depending on the immune status of the individual, i.e., naive or RV experienced. For this purpose, a two-color virus-like parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…We found that the proportion of RV VP6-specific B cells that are memory cells represents a lower frequency and a less frequently isotype-switch phenotype compared with the proportion of randomly selected B cells that are memory cells. This high proportion of naive B cells in virus-specific clones in the circulation during infection, even in adults who likely have a history of many previous RV infections, is curious and unexplained (14,15,17). We showed previously a high frequency of naive B cells in the VP6 repertoire in adults, and a reduced frequency of somatic mutations in VP6-specific IgD Ϫ memory B cells (15,17).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…We found that the proportion of RV VP6-specific B cells that are memory cells represents a lower frequency and a less frequently isotype-switch phenotype compared with the proportion of randomly selected B cells that are memory cells. This high proportion of naive B cells in virus-specific clones in the circulation during infection, even in adults who likely have a history of many previous RV infections, is curious and unexplained (14,15,17). We showed previously a high frequency of naive B cells in the VP6 repertoire in adults, and a reduced frequency of somatic mutations in VP6-specific IgD Ϫ memory B cells (15,17).…”
Section: Discussionmentioning
confidence: 69%
“…These findings are in agreement with more phenotypic studies in the literature that suggest RV VP6 is a unique Ag. For example, Parez et al (14) reported that a large fraction of human naive B cells interacts with RV VP6 via surface Igs, and these VP6-reactive B cells were detected at similarly high frequencies in adult, infant, and neonatal samples. In mice, Blutt et al (7) also showed robust activation of naive B cells, but not T cells, in Peyer's patches and mesenteric lymph nodes during early RV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the earlier cells observed here may result from the activation of the IgD + B cell fraction reacting with 2/6-VLP that was detected in NALT and CLN. Such cells present in all the lymphoid tissues analyzed from non-immune mice have already been reported within murine splenic cells [11] and, recently, within human B cells from adults, infants and cord blood, and have been proposed to be responsible for an innate B cell response resulting from the interaction of 2/6-VLP with natural surface anti-VP6 Ab [19,20]. Thus, the high frequency of 2/6-VLP-specific B cells observed here may result from both innate and adaptive B cell responses.…”
Section: Igdmentioning
confidence: 99%